Pair negotiation when developing english speaking tasks (2011)
This study analyzes what characterizes the negotiations of seventh graders at a public school of Bogota when working in pairs while developing speaking tasks in EFL classes. The inquiry is a descriptive case study that follows the qualitative paradigm. We conducted the study with four participants, two pairs. The data were collected through video recording transcriptions and a semi-structured students interview. Our pedagogical implementation consisted in proposing the pair work strategy with diverse speaking tasks as content. As a result of the processes of data analysis and interpretation we obtained four consecutive steps that characterize students negotiations: Establishing a connection with a partner to work with, proposing practical alternatives, refusing mates propositions, and making practical decisions. The constant performance of the process of negotiation leads students to construct a sociolinguistic identity that allows agreements to emerge.